Mapping the spread of Avian Influenza Virus in Poultry at Polewali Mandar Regency, 2008-2013 - Aminah Hajah Thaha; Juliawati Rauf; Isnaniah Bagenda (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2018)
The spread of Avian Influenza (AI) virus have a significant impact on the decline in the bird population, economic losses, and food safety. The purpose of this study was to determine level and patterns of distribution AI in chicken at Polewali Mandar Regency, period 2008-2013. The results showed that in 2008 to 2013 cases of poultry deaths by AI has spread in 13 districts of the total 16 districts and 53 villages of the total 167 villages in Polewali Mandar Regency. It shows that 81,25% of district and 31,74% of villages in Polewali Mandar has been infected with AI.  The number of deaths of poultry caused AI period 2008 to 2013 is 49,182. The chicken that are infected native chicken, broiler, ornamental chickens (Philipin), cuckoo, rooster, and ducks. The chicken reared in backyard and commercial poultry sector 3 with the number of chicken are 10-10000. Trend increase in cases of poultry death by AI period 2008 to 2013 in Polewali Mandar generally occurs in January, February, March, July, September, November, and December.